METODE ALOKASI PRODUKSI PADA SUMUR GAS MULTIWELL DAN MULTILAYER DI LAPANGAN âXâ DENGAN DATA TERBATAS - Dewi Fairuz Adam, Nikita
Nowadays in petroleum industry, commingle production becomes a common process.Where multilayer present in a reservoir, the most economical development plans often involve commingling the production of all the layers. In a field with lower productivity production tests rarely held, thus less data available. In these situations, it is challenging to determine the individual flow rates from each layer of the well because of the uncertainties. Reservoir gas in “X” field was used for this paper and having problem with data availability. Only production gas rate total available from all wells in “X” Field without gas production rate from each well. Wells in “X” Field are produced by commingling????the layers also without reservoir pressure and flowing bottomhole pressure available. Production allocation methods from this paper was divided into two major parts. First one is production allocation per well based on dry gas through choke correlation which used data from choke size, downstream and upstream pressure from choke. The next part is production allocation per layer based on pressure-squared approach which used DST data from each layer. The result from using the methods which described from this paper is production allocation for each layer in a commingle gas completion. Also, reservoir pressure and flowing bottomhole pressure for each layer could be obtained by using this method.